Radiographic Study of the Fifth Metatarsal for Optimal Intramedullary Screw Fixation of Jones Fracture. (March 2015) - Ochenjele, George; Ho, Bryant; Switaj, Paul J.; Fuchs, Daniel; Goyal, Nitin; Kadakia, Anish R.
Background: Jones fractures occur in the relatively avascular metadiaphyseal junction of the fifth metatarsal (MT), which predisposes these fractures to delayed union and nonunion. Operative treatment with intramedullary (IM) screw fixation is recommended in certain cases. Incorrect screw selection can lead to refractures, nonunion, and cortical blowout fractures. A better understanding of the anatomy of the fifth MT could aid in preoperative planning, guide screw size selection, and minimize complications. Methods: We retrospectively identified foot computed tomographic (CT) scans of 119 patients that met inclusion criteria. Using interactive 3-dimensional (3-D) models, the following measurements were calculated: MT length, "straight segment length" (distance from the base of the MT to the shaft curvature), and canal diameter. Results: The diaphysis had a lateroplantar curvature where the medullary canal began to taper. The average straight segment length was 52 mm, and corresponded to 68% of the overall length of the MT from its proximal end. The medullary canal cross-section was elliptical rather than circular, with widest width in the sagittal plane and narrowest in coronal plane. The average coronal canal diameter at the isthmus was 5.0 mm. A coronal diameter greater than 4.5 mm at the isthmus was present in 81% of males and 74% of females. Conclusion: To our knowledge, this is the first anatomic description of the fifth metatarsal based on 3-D imaging. Excessive screw length could be avoided by keeping screw length less than 68% of the length of the fifth metatarsal. A greater than 4.5 mm diameter screw might be needed to provide adequate fixation for most study patients since the isthmus of the medullary canal for most were greater than 4.5 mm. Clinical Relevance: Our results provide an improved understanding of the fifth metatarsal anatomy to guide screw diameter and length selection to maximize screw fixation and minimize complications.